The Role of Family Quality Time in Developing Independence in Children Aged 4-6 Years (Phenomenology in Pilangsari Village, Cirebon Regency) - Shahilra Aurelly; Naili Rohmah (Universitas Syiah Kuala, 2025)
This study examines the role of family quality time in fostering independence in children aged 4-6 years, as well as the challenges in implementing family quality time. The research aims to analyze the role of family quality time in developing independence among children aged 4-6 in Pilangsari Village, Cirebon Regency. Early childhood independence serves as a crucial foundation for their social, emotional, and cognitive development. This study employs a qualitative approach, specifically phenomenology, to understand the subjective experiences of parents and children in spending quality time together and its impact on children's independence. Data was collected through observation, in-depth interviews with one family, and participatory observation. The findings indicate that family quality time filled with activities such as playing together, doing household chores, and open communication can enhance children's self-confidence, initiative, and problem-solving skills. Supporting factors, such as the involvement of both mother and father and consistent routines, further strengthen children's independence. These findings have important implications for parents and educators in creating a family environment that supports early childhood independence through meaningful interactions.